Activities to Foster The Students’ Socio-pragmatics Awareness: a Locally Situated Process - Fitri Wijayanti; Alfi Hidayatu Miqawati (Politeknik Negeri Jember, 2022)
Equipping students with Sociopragamatic awareness is very crucial to be deployed. Since Sociopragmatic competences are required in communications, the ELT teachers need to facilitate them with engaging activities and authentic material. Making the students engage actively in classroom instruction will increase their enthusiasm and spread the positivity among the students. However, inserting Socioragmatic into classroom instruction is rarely to be implemented by the teachers. To fill this void, the article presents activities to arouse the students Sociopragmatic awareness through locally situated process. This process is implemented in form of Discourse Completion Task (DCT), movie clips, and comic strips. These classroom activities are believed to give opportunities for the students to experience language practices therefore they know how to use the sensitive English.